Reviving the gobbet: venerable sophistication for contemporary media literacy - Kevin Hora (Irish Journal of Academic Practice)
This paper suggests that a technique for close textual reading used in history, the classics and theology for two almost two centuries, the gobbet, can be repurposed as a method of developing media literacy in higher education students in other disciplines. The gobbet is a bite-sized extract from a longer set text learners have studied that acts as an entry to the whole text, permitting critical, contextualised evaluation to take place. As a pedagogical tool, the gobbet can be a counterweight to discontinuous reading practices and abstracted information sources. It is highly effective for analysing contemporary media and discourse, in producing articulate learners confident in their ability to analyse information, and in developing transferrable critical and communication skills for scholarly, career and personal use. This paper situates the gobbet, reframed for modern use in an expanded range of scholarly disciplines, as a learner-centric method that develops agency and independence within a phenomenographic pedagogical frame.